Editorial - Mani, Alice (Ushus Journal of Business Management, 2021)
The world has registered a remarkable economic progress during the past century and a half. But, the economic growth has not been a steady upward swing or a smooth and progressive. movement. Every business house - be it a manufacturing unit or a software service firm -has experienced upward and downward swings. Periods of prosperity have alternated periods of adversity. The dawn of the new millennium has ushered in several structural changes in the Indian and World economy, thus minimising the impact of certain environmental factors on business and bringing to focus some hitherto less significant forces. Global environment has suddenly become all too important and technological boom, too, is assuming greater relevance. The current journal has been brought out issues related to the challenges and opportunities in the new millennium as an effort at incorporating and understanding the shifts and changes in the business atmosphere covering finance, marketing, management, stress on managers and executives, the social impact of business actions, eco-friendliness, women executives and the more recently developed world wide web, which has shrunk the world by its sheer speed and effectiveness. The journal aims at reflecting the popular mood of businessmen who are busy scouting the globe for joint ventures, while other venture-seekers are doing their rounds in search of newer avenues to set up their business points. The time is rife now for all organisations and educational institutions to seek newer outlets to preserve their resources and to share their achievements while trying to aid in the transformation of society's needs into more purposeful existence, rather than to ignore the surrounding environment and encourage self-destruction.